Online Promotion And Perceived Quality On Consumer Purchasing Decisions - Rini Lestari; Niar Astaginy; Muhamad Stiadi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
The objective of this study is to examine the impact of online promotion and perceived quality on consumer purchasing behavior at the Mutiara Famouse Kolaka Store. The present study employs a survey research design, utilizing a questionnaire as the primary data collection instrument. The study's population consisted of consumers who had engaged in shopping activities at the renowned Kolaka Mutiara Shop. A purposive sampling technique was employed to select 120 respondents, which involves selecting individuals based on specific criteria. The employed data collection methodology encompassed both primary and secondary data sources. The data collected was subjected to analysis using Partial Least Squares (PLS) analysis techniques, utilizing the Smart PLS program. The findings of this study indicate that internet promotional activities exert a favorable and statistically significant impact on customer buying behavior. This is supported by the T-Count or T-Statistics, specifically 5.276 and a P Value of 0.000. The variable of Perceived Quality exhibits a statistically significant and positive impact on consumer purchasing decisions, as evidenced by the T-Count value of 2.538 and a corresponding P Value of 0.006. Based on the obtained results, it can be inferred that the variables of Online Promotion and Perceived Quality exhibit a statistically significant positive impact on Consumer Purchasing Decisions. This conclusion is drawn based on the research's adoption of the criterion T-Statistics > 1.64, with a significance level and P Value of less than 0.05. The factors of Online Promotion and Perceived Quality exhibit a statistically significant positive impact of 76.2% on Consumer Purchasing Decisions.